The Historical Development of Madrasah Aliyah Alkhairaat Parigi and Its Contribution to Islamic Education in Central Sulawesi - Nuriyati Nuriyati; Minarni Nongtji; Hasan Hasan; Haliadi Haliadi (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
: This study examines the historical establishment and development of Madrasah Aliyah Alkhairaat Parigi from 1990 to 2025 within the socio-religious context of Islamic education in Central Sulawesi. The research was motivated by the important role of Alkhairaat institutions in expanding Islamic education in Eastern Indonesia and the limited scholarly attention given to the local history of Madrasah Aliyah Alkhairaat Parigi. This study employed a qualitative historical research approach using heuristics, source criticism, interpretation, and historiography. Data were collected through in-depth interviews with founders, school leaders, and historical actors, as well as field observations and institutional documentation. The findings reveal that the establishment of Madrasah Aliyah Alkhairaat Parigi in 1990 was driven by the urgent educational needs of the Muslim community in Parigi Moutong Regency and supported by collective participation from religious leaders and local society. The madrasah developed gradually despite limited facilities and financial resources during its early years. Over time, the institution became an important center for Islamic education, moral formation, and community empowerment. The study also demonstrates that the madrasah played a significant role in preserving Alkhairaat educational traditions, strengthening Islamic identity, and improving educational access in Central Sulawesi. This research contributes to the historiography of Islamic education by highlighting the importance of local Islamic institutions in educational and socio-cultural transformation within Indonesian Muslim society